2004
DOI: 10.1113/jphysiol.2004.068924
|View full text |Cite
|
Sign up to set email alerts
|

Quantal release of ATP from clusters of PC12 cells

Abstract: Although ATP is important for intercellular communication, little is known about the mechanism of endogenous ATP release due to a dearth of suitable models. Using PC12 cells known to express the P2X2 subtype of ATP receptors and to store ATP with catecholamines inside dense-core vesicles, we found that clusters of PC12 cells cultured for 3-7 days generated small transient inward currents (STICs) after an inward current elicited by exogenous ATP. The amplitude of STICs in individual cells correlated with the pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
33
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(36 citation statements)
references
References 50 publications
(84 reference statements)
3
33
0
Order By: Relevance
“…Finally, we investigated whether SLC17A9 is responsible for vesicular storage and subsequent exocytosis of ATP in purinergic cells. PC12 cells are known to store and secrete ATP through secretory granule-mediated exocytosis (24). We found that mSLC17A9 protein was associated with secretory granules (Fig.…”
Section: Involvement Of Slc17a9 Protein In Vesicular Storage and Exocmentioning
confidence: 75%
“…Finally, we investigated whether SLC17A9 is responsible for vesicular storage and subsequent exocytosis of ATP in purinergic cells. PC12 cells are known to store and secrete ATP through secretory granule-mediated exocytosis (24). We found that mSLC17A9 protein was associated with secretory granules (Fig.…”
Section: Involvement Of Slc17a9 Protein In Vesicular Storage and Exocmentioning
confidence: 75%
“…In a similar fashion, clusters of PC12 cells display such 'autaptic' behaviour, as detected by spontaneous transient inward currents (STICs) through P2X 2 receptors. There is firm evidence that this phenomenon reflects quantal exocytotic release of ATP from PC12 cells [2]. In addition, the discovery of pannexin 1 as an ATP-releasing channel in taste bud epithelia convincingly used the P2X2/3 biosensor approach [10].…”
Section: P2x 2 Receptor-mediated Ion Currents As Biosensors For Extramentioning
confidence: 99%
“…It is thus established that, e.g. chromaffin cells and the closely related PC12 cells store large amounts of ATP (>100 mM) together with catecholamines [2,102], that insulin secretion from B cells occurs together with ATP [17] and that α-dense granules in thrombocytes contain very high concentrations of ADP, a known key factor in thrombus formation [14]. There is strong evidence that astrocytic release of nucleotides under physiological conditions involves an exocytotic mechanism [45,103,104], in contrast to the above-mentioned controversial issue of connexon hemichannel-mediated ATP release from astrocytes under non-physiological situations [36].…”
Section: Vesicular Release Of Nucleotidesmentioning
confidence: 99%
See 2 more Smart Citations